2013
DOI: 10.9790/3008-0556366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyherbal Formulation in Treatment of Poly Cystic Ovarian Syndrome (PCOS)

Abstract: Poly cystic ovarian syndrome (PCOS) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It also possesses anti-inflammatory activity on the granulosa layer of the corpus luteum. 35 , 36 , 37 From the results, it can be identified that the polyherbal formulation in all the doses i.e., 500, 750 and 1000 mg/kg does not show any significant changes in the various parameters associated with the PCOS. Thus, it can be stated that the polyherbal formulation at the dose of 500 mg/kg can be effective in the treatment and prevention of PCOS.…”
Section: Discussionmentioning
confidence: 94%
“…It also possesses anti-inflammatory activity on the granulosa layer of the corpus luteum. 35 , 36 , 37 From the results, it can be identified that the polyherbal formulation in all the doses i.e., 500, 750 and 1000 mg/kg does not show any significant changes in the various parameters associated with the PCOS. Thus, it can be stated that the polyherbal formulation at the dose of 500 mg/kg can be effective in the treatment and prevention of PCOS.…”
Section: Discussionmentioning
confidence: 94%